Local economic development opportunities from NHS spending: Evidence from Wales. (October 2017) - Morgan, Kevin; Munday, Max; Roberts, Annette
The article examines the local and regional economic impacts of NHS spending. The research is set in the context of tensions between buying economies, process efficiencies and local economic development impacts of public sector procurement, and contributes to the evidence base on supplier proximity and income retention at the local and regional level. The scale, scope and spatial distribution of NHS spending in a South Wales case are analysed using detailed purchasing information provided by a local health board. The article then uses an economic modelling framework to quantify the supply chain impacts of this spending to determine the full regional economic impacts of operational and capital expenditures. The analysis shows that NHS Wales spending supports significant levels of regional economic activity in terms of output, employment and gross value-added. The article also explores scenarios on the potential economic significance of import substitution of selected purchases. The implications of the changing procurement environment, with new EU directives, and a reorganisation of procurement functions within NHS Wales, are explored, and suggestions are made for further research.